Branched-Chain Amino Acid (BCAA) Oligopeptide Determination from Whey Proteins: Preparation, Peptide Profiles, and Anti-Fatigue Activity - Qiong Zhu; Renjie Zhou; Xiping Zhu; Xiangru Lu; Binli Ai; Qibin Zhuang; Chun Cui (Foods)
Whey proteins have anti-fatigue activity, but there are few studies that have reported the ameliorative effects of branched-chain amino acid (BCAA) oligopeptides from whey proteins on fatigue in mice. The purposes of this study were to establish a process for the preparation of BCAA oligopeptides from whey protein and to investigate the anti-fatigue activity of BCAA oligopeptides. Whey proteins were hydrolyzed by trypsin and flavourzyme and purified by ethanol precipitation and reversed-phase high performance liquid chromatography (RP-HPLC). Fraction D’ was found to contain the highest content of BCAAs and a high proportion of low-molecular-weight peptides (<1 kDa; content: 81.48%). Subsequently, mass spectrometry identified 15 BCAA oligopeptides in Fraction D’, including three dipeptides, six tripeptides, two tetrapeptides, and four pentapeptides. In addition, animal experiments showed that BCAA oligopeptides significantly prolonged the residence time on the rod and swimming time of mice. Further studies showed that BCAA oligopeptides remarkably reduced serotonin (5-hydroxytryptamine, 5-HT) synthesis in the brain by down-regulating the plasma-free tryptophan (F-Trp)/BCAA ratio, thereby alleviating fatigue. Therefore, BCAA oligopeptides can be used as an auxiliary functional dietary molecule in functional products to exert anti-fatigue activity by regulating 5-HT synthesis.